Pengaruh Karakteristik Lalu Lintas Terhadap Kebisingan Jalan Raya - Lakawa, Irwan; Sufrianto, Sufrianto; Syamsuddin, Syamsuddin; Rahman, Irwanto (Universitas Sulawesi Tenggara, 2023)
The availability of transportation facilities in urban areas strongly supports community activities and mobility from one land use to another. The increase in the number of motorized vehicles causes an increase in noise level on the highway. The purpose of this study was to analyze the traffic characteristics on Ahmad Yani street Kendari City, noise level, and partial effect of traffic characteristics on the noise level. The research method uses descriptive and parametric statistical approaches. The results showed that the average traffic volume on Ahmad Yani street was 1179 pcu/hour, with a composition of motorcycles 59%, light vehicles 37%, and heavy vehicles 4%. The average vehicle speed is 48 km/hour and average traffic density is 51 pcu/km. The highest noise level occurred in the school area of 76.1 dB, while the lowest occurred in the trading area of 70.5 dB. The average noise level on the Ahmad Yani street is 73.4 dB. The effect of vehicle volume on the noise level is 56.7%, vehicle speed on the noise level is 53.4%, and the traffic density on the noise level is 68.7%. This shows that the traffic density variable has the greatest influence on the noise intensity on the highway, followed by vehicle volume variable, and the lowest is vehicle speed variable.